Asymmetric synthesis of epohelmins A, B and 3-epi ent-epohelmin A. Issue 49 (8th December 2016) - Si, Chang-Mei; Liu, Yi-Wen; Mao, Zhuo-Ya; Han, Pan; Du, Zhen-Ting; Wei, Bang-Guo
Abstract: An efficient method for asymmetric synthesis of epohelmins A (3 ), B (4 ) and their isomer24 is detailed in this report. The key feature in this divergent synthesis includes the SmI2 -induced cross-coupling of N - tert -butanesulfinyl imine10 with chiral aldehyde9 derived fromd -malic acid. A cascade cyclization to the pyrrolizidine skeleton is achieved in our synthetic route for epohelmins. In addition, an interesting intramolecular oxa-Michael addition was observed for epohelmin A (3 ). Graphical abstract: